Simvastatin Increases the Activity of Endothelial Nitric Oxide Synthase via Enhancing Phosphorylation - 李小霞 汪培华 徐西振 王勇 夏永 汪道文 (Journal of Huazhong University of Science and Technology. Medical sciences, 2009)
3-hydroxy-3-methylgulutaryl-coenzyme A （HMG-CoA） reductase inhibitors or statins are a kind of lipid-lowering agents and have been used for the prevention and treatment of Cardiovascular diseases. Recent studies suggested that statins, besides lowering cholesterol, may protect vessels by enhancing the activity of endothelial nitric oxide synthase （eNOS）. In the present study, we investigated if simvastatin increases eNOS activity through its phosphorylation in 293 cells （293-eNOS） with stable expression of eNOS. The results showed that incubation of 293-eNOS cells with simvastatin （10 μm/L） for 2 h significantly increased in the activity of eNOS as shown by the conversion of L-arginine to L-citrulline （2889.70±201.51 versus 5630.18＋218.75 pmol/min . mg proteins） （P〈0.01）. Western blotting revealed that simvastatin increased phosphorylation of eNOS at 1177 （ser） and also 495 （thr） but did not affect the overall expression of eNOS or inducible NOS. Further study found that simvastatin raised phosphorylation levels of Akt and AMPK, and such effect could be antagonized by Akt inhibitor or AMPK inhibitor. These results suggest that simvastatin could stimulate,the activity of eNOS via its phosphorylation by Akt and AMPK, which provides a new mechanism, other than lipid-lowering effect, for the cardiovascular protection of statins.